2014
DOI: 10.1105/tpc.114.126607
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Site-Specific DNA Double-Strand Breaks in Barley Occurs via Diverse Pathways Primarily Involving the Sister Chromatid

Abstract: ORCID IDs: 0000-0001-7080-7983 (J.K.); 0000-0002-6300-2068 (I.S.)DNA double-strand break (DSB) repair mechanisms differ in their requirements for a homologous repair template and in the accuracy of the result. We aimed to quantify the outcome of repair of a single targeted DSB in somatic cells of young barley (Hordeum vulgare) plants. Amplicon sequencing of three reporter constructs revealed 47 to 58% of reads as repaired via nonhomologous end-joining (NHEJ) with deletions and/or small (1 to 3 bp) insertions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 42 publications
0
59
0
Order By: Relevance
“…For OsAOX1c and Os BEL , short changes (≤ 3 bp) were the major type of mutation; conversely, all mutations in OsAOX1a were relatively long deletions. Because short deletions are often associated with classical NHEJ (cNHEJ) and longer deletions may represent the results of microhomology-mediated end-joining (or alternative NHEJ, aNHEJ)3738, the CRISPR/Cas9-induced mutation patterns might be different for specific DSB sites through distinguished NHEJ repair pathway.…”
Section: Resultsmentioning
confidence: 99%
“…For OsAOX1c and Os BEL , short changes (≤ 3 bp) were the major type of mutation; conversely, all mutations in OsAOX1a were relatively long deletions. Because short deletions are often associated with classical NHEJ (cNHEJ) and longer deletions may represent the results of microhomology-mediated end-joining (or alternative NHEJ, aNHEJ)3738, the CRISPR/Cas9-induced mutation patterns might be different for specific DSB sites through distinguished NHEJ repair pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many inserted sequences at I-SceI break sites have been shown to be templated from sequences near the DSB sites and to be rejoined via MMEJ; therefore, a model termed synthesisdependent MMEJ has been proposed (Yu and McVey, 2010). On the other hand, it has been demonstrated that sequences from elsewhere in the genome or around the DSB site may be inserted into I-SceI break sites in exogenous genes via a synthesisdependent strand annealing (SDSA)-like model in tobacco (Salomon and Puchta, 1998) and barley (Vu et al, 2014). These findings have suggested that the SDSA-like model may result in insertions within DSB sites by homology search via microhomology and copying from sister chromatid DNA.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest that the barley genome is still quite dynamic. In particular, the frequent occurrence of INDELS in non-coding regions point to the importance of DNA damage repair by erroneous pathways in barley, as suggested (Vu et al, 2014). In addition, the high degree of sequence divergence between cultivars could have impacted gene targeting efficiencies if isogenic ALS gene DNA had not been used.…”
Section: Discussionmentioning
confidence: 83%